Increased Posterior Tibial Slope and its Association with ACL Rupture in the Pediatric Population. Issue 7 (29th July 2014) - O'Malley, Michael P.; Milewski, Matthew David; Solomito, Matthew; Erwteman, Andrew; Nissen, Carl W.
Objectives: Particular interest has been placed in identifying risk factors for sports related injuries in younger populations. In regards to the relationship between posterior sagittal slope of the tibia as a potential risk factor for ACL injury in the pediatric population, studies at this time remain limited.The purpose of our study is to investigate this relationship between posterior tibial slope and ACL rupture in the pediatric population. Our null hypothesis states that an increased posterior tibial slope does not serve as a contributing risk factor for ACL rupture in pediatric patients with open physes. Methods: A retrospective case-control study was performed at an academic pediatric sports medicine center comparing a target population of skeletally immature patients with an ACL rupture with an age-matched control group. Posterior tibial slope was then measured on plain lateral radiographs in both groups by blinded readers (Figure 1), at two separate time intervals, utilizing a previously examined and accepted technique. Results: Thirty two patients were included in the ACL rupture with open physes group (average age 13 years old, range 9-17) and compared to 32 patients in the control group (average age 13 years old, range 9-16). These groups were also similar in regards to male:female and left:right distribution. The mean posterior tibial slope in the ACL injured population was 10.0° ± 3° versus 8.5° ± 3° in the control group. Statistical significance was seen in comparing slope measurements between the ACL injury and control groups in two of the three readers (Readers 1 and 3) at both time points (Reader 1: p = 0.0348, p = 0.0051; Reader 3: p = 0.0009, p = .0059). Intra-rater proved superior with values correlating with moderate-to-good reliability (Reader 1 ICC = 0.7387, Reader 2 ICC = 0.8853, Reader 3 ICC = 0.5316), while inter-rater values corresponded with fair-to-moderate reliability (Measure 1 ICC = 0.4657, Measure 2 ICC = 0.5146). The average female posterior tibial slope was 9.5° (range of 3-14°) and similar to the posterior tibial slope for males, which was 9.8° (range of 2-16°). Conclusion: The authors reject the null hypothesis and these results uphold that an increased posterior tibial slope serves as a possible risk factor for ACL rupture in a skeletally immature population.